Skincare Product Safety Regulations in Indonesia and Asian Countries within the Framework of International Legal Standards - Luna, Laurenzia; Christabelle, Vanessa; Wijaya, Vicanty; Elsputri, Virginia Chieko (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
This study is driven by the rapid expansion of the global cosmetics trade, which necessitates the alignment of national regulations with international legal standards, particularly in relation to skincare product safety. The objective of this research is to examine Indonesia’s administrative regulations on skincare safety, compare them with those of selected East Asian countries, and evaluate their conformity with international legal frameworks. Employing a qualitative approach, this study utilizes descriptive-comparative analysis of national legal instruments, international standards, and relevant academic literature. The findings reveal that Indonesia has adopted the ASEAN Cosmetic Directive (ACD) harmonization framework; however, its implementation continues to encounter challenges in areas such as regulatory oversight, bureaucratic processes, and technical capacity. In comparison with Japan, South Korea, and China, Indonesia’s regulatory framework remains less integrated. The study concludes that strengthening institutional capacity and enhancing regulatory harmonization are essential to achieving greater alignment with the WTO’s Technical Barriers to Trade (TBT) principles and other international standards.